Effect of Aeroelastic Tailoring Design on Wing Mode - Yajuan He; Junli Wang; Jinyang Li; Bofeng Duan; Yang Zhou; Kangjie Wang (International Journal of Aerospace Engineering)
In this paper, in order to clarify the influence of structural parameters of laminates on the modal characteristics of high-aspect-ratio wings under prestress, the CFD/CSD coupling method was used to study the modal characteristics of nonlinear structures under the influence of layering angle, layering unbalanced coefficient, and layering reference direction. The results show that the first six order modal frequencies of wing structure increase with the increase of layering angle, and the increment change of frequency increases with the increase of layering angle. The frequency results of positive and negative layering angles are basically the same, and there is no great difference. The modal frequency of airfoil structure is not very sensitive to the change of unbalanced coefficient. The modal frequencies obtained by the mixed angle layering scheme are obviously larger than those obtained by the layering scheme composed of only two angles. With the change of the reference direction of laying, the lowest frequency is generally present in the 0° reference direction and has one or two minima in each order of modal frequency. The layer reference direction angle mainly in the second quadrant is beneficial to the enhancement of modal frequency. After determining the related layer parameters, the appropriate adjustment of the layer reference direction will be beneficial to change the vibration characteristics of the wing structure.